Anaesthetic Management of Patients with COVID-19: A Single Center Initial Experience from Nepal - Piya, Roshan; Shrestha, Anil; Shrestha, Gentle Sunder; Amatya, Sirish Prasad; Shrestha, Abisesh; Barahi, Sunti; Thapa, Subarna Dhoj (Journal of Nepal Health Research Council, 2020)
Anaesthetic management of patients with Corona Virus Disease (COVID-19) posses multiple challenges. In the low-income nation like Nepal, factors like suboptimal infrastructure and resource limitations may add on to the existing challenges. Proper planning and preparedness can help to overcome the challenges and enhance safety of both the patients undergoing surgery and of the health care workers involved in patient management.Keywords: Anaesthetic management; COVID-19; Nepal